ANALYZING THE PROCESS OF TRANSLATION OF ENGLISH COMPOUND WORDS INTO INDONESIAN - OKTAVIANA SIMANJUNTAK; NINGSIH NOVI YANTI TAMBUNAN; SEPTRINA PUTRI D. HUTABARAT; DONI GIBSON SIBURIAN; ROTUA JUNITA SIHOMBING (CV KULTURA DIGITAL MEDIA, 2022)
There are many translation processes in translating a source language into the target language. The translation is done without changing the original meaning of the word from the source language. This research was conducted using a qualitative method because it did not use numbers. The research was taken by using compound words as examples of words to be translated. For this reason, this research was conducted to see the process of translating in English into Indonesian.